Comparison of various procedures in the processing of binucleated-lymphocytes on to glass slide to detect chromosomal breakage (Medical Journal of Indonesia, 2003)
Binucleated lymphocytes can be screened for micronuclei to assess chromosomal damage. There are various procedures to get slides containing binucleated lymphocytes, that are different in harvesting, fixation, and slide preparation methods. Screening binucleated lymphocytes to find a micronucleus needs at least 800 cells with intact cytoplasm. This study aimed to analyze the various procedures and simplified procedures to know which procedure gave the most abundant binucleated lymphocytes with intact cytoplasm and best staining properties for the purpose of micronucleus scoring. Seven heparinized blood samples were obtained from the Dept. of Obstetrics and gynecology, Faculty of medicine, University of Indonesia, Jakarta. The 7 blood samples were subjected to 17 procedures different in harvesting (with or without washing), slide preparation (smear and spot method, and using a cytocentrifuge), and fixation methods (methanol for 1 minute, methanol brief, methanol/glacial acetic acid 3:1 or 9:1). Our results showed that fixatives containing glacial acetic acid are not suitable for micronucleus test. To generate binucleated lymphocytes with intact cytoplasm as much as possible, the procedure should be conducted without washing steps. Methanol fixation either briefly or 1 minute is preferable, and for the ease of screening cytocentrifuge preparation, followed by spot method is preferable. (Med J Indones 2003; 12: 3-7) Keywords: cytokinesis blocked, spot, smear, cytocentrifuge, fixatives